Answer:
x = 4
y = 1
Explanation:
This is a systems of equations problem, and while there are multiple ways to solve, my mind immediately goes to substitution.
x + 2y = 6 is easily converted into the value of x:
x = 6 - 2y
Using this, you can substitute that in for the x of the other equation and solve for y.
3 (6 - 2y) - 2y = 10
18 - 6y - 2y = 10
18 - 8y = 10
-8y = -8
y = 1
If you want the other variable (x), you can just plug in the value of y into any of the original equations.
x + 2(1) = 6
x = 4
I hope this helped!